Foresight model and tool factsheet - Kruseman, Gideon K. (International Maize and Wheat Improvement Center, 2022)
At the behest of CIMMYT's management committee a set of calculation procedures was developed to mix and match divergent data sets for research prioritization purposes. For transparency, reproducibility and re-useability of the procedures and other procedures like these ones, the agri-food data analysis modeling framework (ADAM) was conceived. ADAM is based on the design principle of the separation of data, model switches and calculation rules. ADAM provides insight into historic data sets by recombining information and providing results at a vast variety of possible aggregation levels in a transparent way. The modeling framework can, in principle, operate at a variety of aggregation levels. Currently the focus is on country level as the lowest level of aggregation, because that is the level at which data tends to be available in such a way that it can be made into a comprehensive and comparable format.